2010
DOI: 10.1007/s10561-010-9233-1
|View full text |Cite
|
Sign up to set email alerts
|

Families’ reflections on the process of brain donation following coronial autopsy

Abstract: This study aims to explore families' reflections on their decision to donate brain tissue to the NSW Tissue Resource Centre (NSW TRC), Australia. Specifically, the study aims to investigate respondents' initial reactions to the request for donation, primary reasons for their decision, and subsequent satisfaction levels. Participants were next-of-kin (NOK) contacted between May 2002 and May 2008, on the day of their relative's autopsy, who agreed to donate brain tissue to the NSW TRC for medical research. All 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Much of what is already known about this comes from Australian research that evaluated the responses of next-of-kin to a telephone request made on the day of the necropsy to donate the brain of the deceased (Azizi et al 2006;Garrick et al 2009;Sundqvist et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of what is already known about this comes from Australian research that evaluated the responses of next-of-kin to a telephone request made on the day of the necropsy to donate the brain of the deceased (Azizi et al 2006;Garrick et al 2009;Sundqvist et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the sample studied, 12.5 % of relatives who refused did so because they knew the deceased person's express wish. In a study carried out with relatives who consented to the brain donation, Sundqvist et al (2012) showed that 44 % did not discuss this topic with the deceased person in life, but they identified higher consent rates among families who had previously discussed the topic with their family members and knew their wishes. These findings highlight the importance of discussion of donations with the family and the promotion of positive attitudes toward donation.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study noted that only 24% of families gave their primary reason for agreeing to brain donation as respect for their deceased relative's wishes 5. This undermines the validity of family as substitute decision-makers after death for patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…At least one study regarding success with on-the-spot, “cold-call”, medical examiner brain donations from next-of-kin in Caucasian samples has also been described by the New South Wales Tissue Resource Centre, where approximately 54% of families that were approached consented to brain donation [18] for psychiatric, substance abuse, and neurological disorders. In this same brain donation program of Caucasian brain donation samples, being future organ/transplant donors in other programs [19], or having prior conversations with loved ones about brain/organ donation before their death [20] were positively associated with brain donation.…”
Section: Introductionmentioning
confidence: 99%